Agptru multimetallic nanocrystals, methods of making and applications thereof
Patent Information
- Application Number
- CN202211603350.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-12-13
AI Technical Summary
例如公开号为CN112657507A的中国专利文献公开了一种以活性金属(Pd、Pt、Ir、Ni)为内核,Cu、Sn、Ag、Zn为壳层的核壳结构的双金属催化剂,对于加氢脱氯反应具有高活性与反应选择性,然而其活性金属颗粒尺寸一般在50~60nm,易团聚且活性金属的有效催化面积较小
[0032]本发明采用AgPtRu多金属复合结构纳米颗粒作为脱氯电催化剂,在电催化过程中发挥多金属协同效应,Ag与Ru的添加改变Pt的电子结构,促进脱氯与产物脱附,极大提升了电催化活性,且Ag作为牺牲金属对活性金属Pt有保护作用,Ru本身的抗氯中毒能力也有助于提升多金属纳米晶的电化学稳定性,因此所述的AgPtRu在不必使用更昂贵的Pd的条件下针对水相电解液中的含氯有机污染物仍可进行高效持久的脱氯处理。
Smart Images

Figure CN116121875B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional nanomaterials technology, and in particular to an AgPtRu multimetal nanocrystal, its preparation method, and its application. Background Technology
[0002] Chlorinated organic compounds (COCs) are highly toxic, difficult to degrade, persistent, and bioaccumulative, often exhibiting carcinogenic, teratogenic, and mutagenic effects, thus posing a significant threat to the environment. The key to detoxifying and decomposing COCs is dechlorination. Since the C-Cl bond breaking energy barrier is relatively low on the noble metal Pd, palladium-based composite materials are often used as electrocatalysts for electrochemical dechlorination. For example, Chinese patent document CN113846342A discloses a method for preparing highly dispersed, low-dose Pd nanoparticles supported on an inorganic-organic core-shell framework. This involves dopamine polymerization coating on the surface of a TiO2 nanoarray with a large specific surface area, followed by chemical impregnation to disperse and load Pd nanoparticles onto the core-shell framework surface. The process involves hydrothermal treatment, calcination, dopamine self-assembly, and in-situ reduction. Chinese patent document CN101565356A discloses a method for dechlorinating chlorophenols using a palladium-carbon catalyst; however, the separation of the catalyst from the reactants / products and the need for continuous catalyst activation must be considered. Chinese patent document CN111250106A uses a flower-shaped nano-palladium / foam nickel catalyst for the dechlorination and hydrogenation of chlorinated aromatic compounds, but its noble metal catalytic efficiency still needs to be improved.
[0003] In recent years, with the rising price of Pd, the strategy of combining Pd with cheaper metals to leverage multi-metal synergistic and electronic effects to achieve high catalytic activity and durability has been widely adopted. For example, Chinese patent document CN112657507A discloses a core-shell bimetallic catalyst with an active metal (Pd, Pt, Ir, Ni) as the core and Cu, Sn, Ag, Zn as the shell. This catalyst exhibits high activity and selectivity for hydrodechlorination reactions; however, the active metal particles are generally 50–60 nm in size, making them prone to aggregation and resulting in a relatively small effective catalytic area. Similarly, Chinese patent document CN115323427A utilizes transition metals and palladium to form a multi-component synergistic effect. It synthesizes a metal-organic framework using transition metal compounds of Co, Ni, and Zn with dimethylimidazolium, followed by Pd electrochemical replacement. PdZn exhibits good initial dechlorination activity; however, the synthesis of the metal-organic framework requires a high reaction temperature (700℃ in a tube furnace) and suffers from poor electrocatalytic stability. Summary of the Invention
[0004] This invention provides a composite structure of AgPtRu multimetal nanocrystals that can exert synergistic effects of multiple metals and achieve efficient dechlorination, as well as a method for preparing the same.
[0005] The technical solution of the present invention is as follows:
[0006] A method for preparing AgPtRu multimetal nanocrystals includes the following steps:
[0007] (1) Pt precursor, KCl and surface stabilizer are added to the reaction solvent and dispersed to form a homogeneous reaction solution. Then polyethylene glycol is added, and after heating to 130-150℃, Ag precursor is added. The reaction is stirred for 2-5 hours to generate AgPt octahedral nanocrystals.
[0008] (2) The reaction solution containing AgPt octahedral nanocrystals in step (1) is heated to 150-170°C, and then ruthenium precursor is added. After reacting for 12-36 hours, the mixture is centrifuged and washed to obtain AgPtRu multimetal nanocrystals with a composite structure.
[0009] Preferably, in step (1), the reaction solvent is tetraethylene triethylene glycol. Tetraethylene triethylene glycol can be used as both a reaction solvent and a reducing agent.
[0010] Preferably, based on the reaction solvent, the dosage of Pt precursor is 0.01–0.05 mol / L; the dosage of Ag precursor is 0.01–0.03 mol / L.
[0011] The Pt precursor is platinum acetylacetonate; the Ag precursor is silver trifluoroacetate.
[0012] KCl can effectively regulate the growth kinetics of nanocrystals by controlling the concentration of Ag precursor. Preferably, the molar ratio of KCl to Ag precursor is 5 to 10:1.
[0013] Preferably, the surface stabilizer is hexadecyltrimethylammonium bromide and polyvinylpyrrolidone; the molar ratio of hexadecyltrimethylammonium bromide to the total amount of the two metal precursors is 3 to 10:1.
[0014] The amount of polyvinylpyrrolidone added is 300-800 mg.
[0015] The average molecular weight of the polyethylene glycol is 500-800.
[0016] In a further preferred embodiment, in step (1), polyethylene glycol is preheated before being added to the homogeneous reaction solution. Preheating causes polyethylene glycol to decompose and oxidize, forming ethanol aldehydes of varying concentrations, which can serve as reducing agents in the synthesis of nanocrystals, further regulating the reaction kinetics of AgPt octahedral growth.
[0017] Furthermore, the preheating temperature of polyethylene glycol is 120–150°C, and the preheating time is 0.1–3 hours.
[0018] The Ru precursor is ruthenium trichloride.
[0019] Ruthenium trichloride was added as a solution of ruthenium trichloride in tetraethylene glycol at a concentration of 30–60 mmol / L. The solution was then ultrasonically dispersed to form a relatively uniform black solution. The amount added was 0.5–2 mL (25–30 mL of reaction solvent).
[0020] Preferably, in step (2), the amount of Ru precursor added is 0.5 to 5 mmol / L, based on the reaction solvent of step (1).
[0021] The amount of Ru precursor added will directly affect the composition of the AgPtRu nanocrystal surface. When a higher concentration of Ru undergoes secondary growth, it will form a galvanic cell with Ag in the nanocrystal, resulting in an irregularly hollowed heterostructure under the influence of the Kirkendall effect. Therefore, hollow composite nanocrystals can be obtained without template agents and etchants.
[0022] More preferably, in step (2), the amount of Ru precursor added is 4 to 5 mmol / L, based on the reaction solvent of step (1).
[0023] Step (2) uses the reaction solution from step (1) to directly perform Ru secondary growth. Therefore, the size of the AgPt octahedron obtained in step (1) can directly affect the size of the final AgPtRu nanocrystals, thereby enabling the size control of multi-metal nanocrystals.
[0024] In step (2), the centrifugal washing is performed by washing multiple times with acetone or methanol at a volume of 2 to 4 times. Cyclohexane at a volume of 0.1 to 1 times can be added to increase the centrifugal recovery rate of nanocrystals.
[0025] The present invention also provides AgPtRu multimetal nanocrystals prepared by the above preparation method.
[0026] The preparation method of this invention can effectively control the size, morphology, and surface composition of AgPtRu polymetallic nanocrystals, resulting in AgPtRu polymetallic nanocrystals with a size of less than 20 nm, a large effective catalytic area of the active metal, and a simple and mild preparation process. AgPtRu polymetallic nanocrystals exhibit excellent performance in electrochemical dechlorination and hydrogenation, with good persistence, maintaining high dechlorination activity even after multiple electrolysis cycles.
[0027] The present invention also provides the application of the aforementioned AgPtRu multimetal nanocrystals in the electrochemical dechlorination of chlorine-containing organic pollutants.
[0028] The applications include:
[0029] The AgPtRu multimetal nanocrystals were loaded onto a carbon support to form a working electrode. A Pt electrode was used as the counter electrode and an Ag / AgCl electrode was used as the reference electrode to electrolytically dechlorinate chlorine-containing organic pollutants.
[0030] Preferably, constant potential electrolysis is performed with a potential of -0.85V vs. Ag / AgCl, an electrolysis temperature of 25-30℃, a single electrolysis time of 3-8h, and the electrolyte containing chlorine-containing organic pollutants is replaced each time during the electrolysis cycle.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0032] This invention employs AgPtRu multi-metal composite nanoparticles as a dechlorination electrocatalyst, which exerts a multi-metal synergistic effect during the electrocatalytic process. The addition of Ag and Ru alters the electronic structure of Pt, promoting dechlorination and product desorption, and greatly enhancing the electrocatalytic activity. Furthermore, Ag, as a sacrificial metal, protects the active metal Pt, and Ru's resistance to chlorine poisoning also helps improve the electrochemical stability of the multi-metal nanocrystals. Therefore, the AgPtRu described herein can still perform efficient and sustained dechlorination treatment of chlorine-containing organic pollutants in aqueous electrolytes without the need to use more expensive Pd.
[0033] The preparation method of this invention is simple, mild, easy to scale up, produces high-quality Pt with strong electrocatalytic persistence, and can achieve higher economic benefits when applied to the electrocatalytic dechlorination reaction of chlorinated organic compounds. Attached Figure Description
[0034] Figure 1 Transmission electron microscopy images (scale bar: 50 nm) and size distribution diagrams of the size-controllable AgPtRu metal nanocrystals prepared in Example 1.
[0035] Figure 2 The images show transmission electron microscopy (TEM) images (a) and high-resolution TEM images (b) of single AgPtRu hollow metal nanocrystals prepared in Example 2.
[0036] Figure 3 The image shows the XRD pattern of the metal nanocrystals prepared in Example 2.
[0037] Figure 4 The graph shows the dechlorination performance of the metal nanocrystals prepared in Example 2.
[0038] Figure 5 The images shown are transmission electron microscopy (TEM) images (a) and high-resolution TEM images (b) of single AgPtRu metal nanocrystals prepared in Example 3.
[0039] Figure 6 The graph shows the dechlorination efficiency of the metal nanocrystals prepared in Example 3 after 30 dechlorination cycles. Detailed Implementation
[0040] Example 1
[0041] In a 250 mL glass reaction vessel, 25 mL of tetraethylene glycol, 0.5 mmol of platinum acetylacetonate, 225 mg of KCl, 100 mg of cetyltrimethylammonium bromide, and 300 mg of polyvinylpyrrolidone were added. The mixture was ultrasonically and magnetically stirred to form a clear, pale yellow homogeneous reaction solution. Then, 15 mL of preheated polyethylene glycol (average molecular weight 600) was added to adjust the concentration of the reducing agent in the system. The reaction system was heated to the set reaction temperature of 145 °C, and 0.3 mmol of silver trifluoroacetate was quickly added. The reaction continued under magnetic stirring. Three reaction solutions were obtained by preheating the polyethylene glycol portion at 140 °C for 3 h, 1 h, and 0 h, respectively. After adding the silver precursor and reacting for 3 h, the reaction temperature was adjusted to 165 °C, and 0.5 mL of a 60 mmol / L ruthenium trichloride solution was added to each solution. After reacting for 24 h, the solution was washed with one volume of cyclohexane and three volumes of acetone, and then centrifuged to recover the product. The concentration difference of ethanol aldehydes caused by the preheating step can control the size of the AgPt octahedral seed crystals obtained in the previous step, thereby affecting the size of the formed AgPtRu nanocrystals.
[0042] The transmission electron microscopy (TEM) images of the three sets of prepared metal nanocrystals are as follows: Figure 1 As shown in (a), (b), and (c), AgPtRu nanocrystals with sizes of 8.5±0.65 nm, 10.42±0.32 nm, and 14.73±1.14 nm were obtained by preheating the polyethylene glycol portion for 3 h, 1 h, and 0 h, respectively (as shown in Figures 1-2). Figure 1 As shown in (a1), (b1), and (c1), the sizes are all excellent, and the two groups of nanocrystals with slightly smaller sizes still retain the octahedral morphology of the AgPt seed crystals, and are named AgPtRu-8.5nm, AgPtRu-10.4nm, and AgPtRu-14.7nm, respectively.
[0043] Three groups of AgPtRu nanocrystals were loaded onto a carbon support (Vulcan C: activated carbon mass ratio of 9:1) to form an electrocatalyst (10 wt% metal mass) modified with hydrophilic carbon paper. Dechlorination tests were conducted in a three-electrode H-type electrochemical cell separated by an N117 cation exchange membrane. The reference electrode was Ag / AgCl, the electrolyte was a 5 mmol / L Na2SO4 solution, and the catholyte had a 2-chlorophenol contaminant concentration of 0.5 mmol / L. A constant-potential electrolysis reaction was performed under magnetic stirring at 200 rpm, with a potential set at -0.85 V vs. Ag / AgCl, at room temperature (25℃). 200 μL of catholyte was collected at fixed electrolysis intervals, filtered, and its component changes were analyzed by high-performance liquid chromatography. The concentration C of 2-chlorophenol was measured after electrolysis for 20 min, 40 min, 60 min, 120 min, and 180 min. t The ratios to the initial concentration (C0 = 0.5 mmol / L) are shown in Table 1. Among them, the smallest AgPtRu-8.5 nm exhibits the best activity, removing 91% of 2-chlorophenol within 3 hours.
[0044] Table 1
[0045]
[0046] Example 2
[0047] In a 250 mL glass reaction vessel, 30 mL of tetraethylene glycol trioxide, 0.6 mmol of platinum acetylacetonate, 225 mg of KCl, 50 mg of cetyltrimethylammonium bromide, and 450 mg of polyvinylpyrrolidone were added. The mixture was ultrasonically and magnetically stirred to form a clear, pale yellow homogeneous reaction solution. Then, 15 mL of polyethylene glycol (preheated to 125 °C, average molecular weight 600) was added to adjust the concentration of the reducing agent in the system. The reaction system was heated to the set reaction temperature of 145 °C, and 0.4 mmol of silver trifluoroacetate was quickly added. The reaction was continued for 3 hours under magnetic stirring. Subsequently, the reaction temperature was adjusted to 165 °C, and 2 mL of a tetraethylene glycol solution containing 60 mmol / L ruthenium trichloride was added. After 30 hours of reaction, the mixture was washed with acetone and methanol, and then centrifuged to recover the solution.
[0048] Transmission electron microscopy (TEM) images and high-resolution electron microscopy (HEM) images of single-particle AgPtRu heterostructured metal nanocrystals prepared are shown below. Figure 2 As shown, due to the high concentration of Ru precursor, a galvanic cell substitution can occur between the Ru precursor and Ag in the nanocrystal seeds, forming a hollow structure in the nanocrystals under the influence of the Kirkendall effect, resulting in a Ru-rich metallic heterostructure on the nanocrystal surface. X-ray diffraction characterization confirms that the AgPtRu hollow nanocrystals are still a face-centered cubic (fcc) multimetallic alloy (see...). Figure 3 This means that Ru is enriched but does not form a metallic phase separation, resulting in a multimetallic heterostructure of Ag, Pt, and Ru.
[0049] Hydrophilic carbon paper was modified with an electrocatalyst (10 wt% metal mass) formed by loading hollow AgPtRu nanocrystals onto a carbon support (Vulcan C: activated carbon mass ratio of 9:1). The catalyst was then used to perform dechlorination tests in a three-electrode H-type electrochemical cell separated by an N117 cation exchange membrane. The reference electrode was Ag / AgCl, the electrolyte was a 5 mmol / L Na2SO4 solution, and the catholyte had a 2-chlorophenol contaminant concentration of 5 mmol / L. The electrolysis reaction was carried out under constant potential electrolysis with magnetic stirring at 200 rpm. The potential was set at -0.85 V vs. Ag / AgCl, and the room temperature was 30 °C. 200 μL of the catholyte was collected at fixed electrolysis intervals, filtered, and the composition changes were analyzed by high-performance liquid chromatography.
[0050] Electrolysis was carried out for 6 hours, followed by 3 cycles, and almost no loss of activity was observed. The current efficiency remained above 25% throughout the process. High-performance liquid chromatography (HPLC) analysis showed that the concentration C of 2-chlorophenol decreased with electrolysis time. t The ratio to the initial concentration (C0 = 5 mmol / L) is as follows: Figure 4 As shown, the dechlorination efficiency of the hollow AgPtRu heterostructure nanocrystalline electrocatalyst can reach over 96% after 6 hours of electrolysis, and the mass activity can reach 16.78 min. -1 g -1 Pt.
[0051] Example 3
[0052] In a 250 mL glass reaction vessel, 25 mL of tetraethylene glycol trioxide, 0.5 mmol of platinum acetylacetonate, 225 mg of KCl, 100 mg of cetyltrimethylammonium bromide, and 600 mg of polyvinylpyrrolidone were added. The mixture was ultrasonically and magnetically stirred to form a clear, pale yellow homogeneous reaction solution. Then, 15 mL of polyethylene glycol (average molecular weight 600) melted only in a hot water bath was added to adjust the concentration of reducing agents in the system. The reaction system was heated to the set reaction temperature of 145 °C, and 0.3 mmol of silver trifluoroacetate was quickly added. The reaction was continued for 3 h under magnetic stirring. Subsequently, the reaction temperature was adjusted to 165 °C, and 1.5 mL of a tetraethylene glycol trioxide solution containing 30 mmol / L ruthenium trichloride was added. After the reaction proceeded for 24 h, the mixture was washed with acetone and centrifuged to recover the solution.
[0053] Transmission electron microscopy (TEM) images and high-resolution TEM images of the prepared AgPtRu metal nanocrystals are shown below. Figure 5As shown, when the concentration of Ru secondary growth is moderately controlled, an octahedral core-shell structure of AgPt@AgPtRu is formed. Hydrophilic carbon paper is modified with an electrocatalyst (10 wt% metal mass) formed by loading AgPtRu nanocrystals onto a carbon support (Vulcan C: activated carbon mass ratio of 9:1). Dechlorination tests were conducted in a three-electrode H-type electrochemical cell separated by an N117 cation exchange membrane. The reference electrode was Ag / AgCl, the electrolyte was tap water, and the cathodic electrolyte had a 2-chlorophenol contaminant concentration of 1 mmol / L. A constant-potential electrolysis reaction was performed under magnetic stirring at 200 rpm, with a potential set at -0.85 V vs. Ag / AgCl, and a room temperature of 30℃. 200 μL of cathodic electrolyte was collected at fixed electrolysis intervals, filtered, and its component changes were analyzed by high-performance liquid chromatography.
[0054] Measurements showed that after 8 hours of electrolysis, the AgPtRu nanocrystals achieved a mass activity of 12.41 min. -1 g -1 Pt exhibits a continuous current efficiency exceeding 15%, and its dechlorination efficiency for 2-chlorophenol reaches over 80%–95% per cycle. Furthermore, after 30 cycles, the electrocatalyst shows virtually no loss of activity. Figure 6 As shown.
[0055] The embodiments described above provide a detailed explanation of the technical solutions and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, additions, and equivalent substitutions made within the scope of the principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing AgPtRu multimetal nanocrystals, characterized in that, Includes the following steps: (1) Pt precursor, KCl and surface stabilizer are added to the reaction solvent and dispersed to form a homogeneous reaction solution. Then polyethylene glycol is added, and after heating to 130~150 ℃, Ag precursor is added. The reaction is stirred for 2~5 h to generate AgPt octahedral nanocrystals. Polyethylene glycol is preheated before being added to the homogeneous reaction solution; the preheating temperature of polyethylene glycol is 120~150 ℃, and the preheating time is 0.1~3 h; (2) The reaction solution containing AgPt octahedral nanocrystals in step (1) is heated to 150~170 °C, and then ruthenium precursor is added. After reacting for 12~36 h, the mixture is centrifuged and washed to obtain AgPtRu multimetal nanocrystals with a composite structure. The composite structure is a hollow heterostructure or an AgPt@AgPtRu core-shell octahedral structure. Based on the reaction solvent of step (1), the dosage of ruthenium precursor is 0.5~5 mmol / L.
2. The method for preparing AgPtRu multimetal nanocrystals according to claim 1, characterized in that, In step (1), the reaction solvent is tetraethylene glycol.
3. The method for preparing AgPtRu multimetal nanocrystals according to claim 1, characterized in that, In step (1), based on the reaction solvent, the amount of Pt precursor added is 0.01~0.05 mol / L; the amount of Ag precursor added is 0.01~0.03 mol / L.
4. The method for preparing AgPtRu multimetal nanocrystals according to claim 1 or 3, characterized in that, The molar ratio of KCl to Ag precursor is 5~10:
1.
5. An AgPtRu multimetal nanocrystal, characterized in that, It is prepared by the preparation method described in any one of claims 1-4.
6. The application of AgPtRu polymetallic nanocrystals as described in claim 5 in the electrochemical dechlorination of chlorine-containing organic pollutants.
7. The application according to claim 6, characterized in that, The AgPtRu multimetal nanocrystals were loaded onto a carbon support to form a working electrode. A Pt electrode was used as the counter electrode and an Ag / AgCl electrode was used as the reference electrode to electrolytically dechlorinate chlorine-containing organic pollutants.
Citation Information
Patent Citations
Method of low-temperature catalytic dechlorination of chlorophenol
CN101565356A
Preparation method of flower-like nano-palladium / foamed nickel catalytic material and application of flower-like nano-palladium / foamed nickel catalytic material in electrocatalytic reduction dechlorination reaction
CN111250106A
High selectivity hydrodechlorination catalyst and preparation method and application thereof
CN112657507A
Inorganic-organic core-shell framework loaded low-dose precious metal palladium material and preparation thereof and application in electro-catalytic dechlorination hydrogenation reaction
CN113846342A
Palladium-based catalyst for electrochemical dechlorination and preparation method thereof
CN115323427A
